2019
DOI: 10.1093/eurheartj/ehz388
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and body composition in relation to 14 cardiovascular conditions in UK Biobank: a Mendelian randomization study

Abstract: Aims The causal role of adiposity for several cardiovascular diseases (CVDs) is unclear. Our primary aim was to apply the Mendelian randomization design to investigate the associations of body mass index (BMI) with 13 CVDs and arterial hypertension. We also assessed the roles of fat mass and fat-free mass on the same outcomes. Methods and results Single-nucleotide polymorphisms associated with BMI and fat mass and fat-free ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
248
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 324 publications
(280 citation statements)
references
References 29 publications
23
248
4
5
Order By: Relevance
“…These conclusions are based on traditional observational studies which are subject to confounding and reverse causality, which are minimized in this MR design. Though a recent MR analysis showed obesity is a key risk factor for cardiovascular disease [3], our study shows obesity is not a consistent risk factor for cancer. This has future implications for public health measures for cancer prevention and screening.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…These conclusions are based on traditional observational studies which are subject to confounding and reverse causality, which are minimized in this MR design. Though a recent MR analysis showed obesity is a key risk factor for cardiovascular disease [3], our study shows obesity is not a consistent risk factor for cancer. This has future implications for public health measures for cancer prevention and screening.…”
Section: Discussioncontrasting
confidence: 91%
“…Obesity is a global epidemic [1], with 20% of the world's population predicted to be obese by 2025 [2]. Multiple studies have demonstrated that obesity is associated with increased risk of cardiovascular [3] [4], liver [5], and musculoskeletal disease [6]. The relationship between obesity and cancer risk has been subject to extensive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Two prior genetic studies have investigated the relationship between obesity and ICH and did not identify any significant associations . To our knowledge, no study has investigated distinct effects between lobar and nonlobar ICH.…”
Section: Discussionmentioning
confidence: 91%
“…Two prior genetic studies have investigated the relationship between obesity and ICH and did not identify any significant associations. 6,7 To our knowledge, no study has investigated distinct effects between lobar and nonlobar ICH. In contrast to ischemic stroke, epidemiologic studies have reported conflicting results on the association between obesity and ICH risk, with 1 study reporting an increased prevalence of obesity in patients hospitalized for ICH 39 and another showing that ICH cases have lower BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation